The Effect of Artificial Intelligence (AI) on Human Capital Management in Indonesia - Btari Mariska Purwaamijaya; Yogi Prasetyo (Jurnal Manajemen dan Kewirausahaan, 2022)
Human resources in an organization is the capital for the organization and its performance is the main indicator for the organization to achieve its goals. In the current digital era, the shift in human resources is demonstrated by the application of Artificial Intelligence (AI) to organizations in Indonesia, both in companies and in several government organizations. A company has a responsibility to its stakeholders to do the job and get the desired profit. However, no research specifically discusses the analysis of the influence of AI (Machine Learning Algorithm, Deep Learning and  Big Data) on Human Capital Management in Indonesia. This study aims to determine the effect of artificial Intelligence (AI) on Human Capital Management in Indonesia. This sample of this study  is 85 respondents of organizational leaders and human resource managers (HR) in Indonesia. It can be concluded that adoption of Deep Learning and  Big Data has a significant  positive impact on Human Capital Management.